Home or Homelessness? Marginal Housing in Vancouver, 1886–1950 - Wade, Jill (Urban History Review / Revue d'histoire urbaine, 1997)
Between 1886 and 1950, marginal housing in Vancouver ran the gamut from home to homelessness: in the spectrum of housing conditions, it could be anything between a room in a lodging house in a respectable suburb and a tea box in a depression-era jungle. Many residents had strong emotional ties to their homes, whatever the quality of housing conditions. Foremost among the reasons for this attachment was a variety of attitudes, concerns, and relationships, including the expectations about adequate housing of those who had lived and worked in British Columbia's resource communities. Examples of these powerful ties, and of the resistance to change that they prompted, suggest that housing bureaucrats and activists should think carefully about the justness and the effectiveness of interventions such as eviction and relocation.